Penyuluhan Program Pencegahan Bullying di LKSA di Yayasan Pendidikan dan Penyantunan Anak Yatim Addinu waddun’ya - Nanda, Marshellino Aurelio; Saputra, Kintan Nabilah (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
This article discusses efforts to prevent bullying at the Child Social Welfare Institution (LKSA) carried out by students of the Faculty of Law, UPN